Effects of particle size and weight percentage of waste rubber crumbs on the performance of compounded tyres - Abdulnabi, Adnan Abbas (2018)
The problem of waste tyre disposal has become a seroius global issue as it has affected not only ecnomy, but also ecology of nations. As such, recycling provieded a powerful solution for the incresing of worn out tyres dumped into the landfills. At current, the recycled rubber produced still has vulcanized rubber structure and low blending ability with the virgin matrix composites. This behaviour limited the scope of engineering applications which could potentially involved recycled rubber material. The aim of this research was to study the effects of waste rubber modification such as size reduction on the manufacturing process of the tread of the passenger tyre. The study followed by construction of finite element code to predict the static and dynamic effects of the tyre material design and modification. Lastly, an empirical model was established to describe the effect of waste crumb rubber incorporation in tyre tread blend. In achieving the first objective Crumb Rubber (CR) modification was investigated, which was the size reduction method. A CR from ambient grinding of the ground tyre was used after it had been subjected to sieve analysis to produce six size categories of 40 μm, 150 μm, 180 μm, 250 μm, 425 μm and 600 μm. Each category was incorporated in different fractions 20 phr, 40 phr and 60 phr (10, 20, 30 wt.%) as a filler in a virgin styrene butadiene rubber (SBR) matrix to examine the effect of CR loading on the properties of the blends produced. The results revealed that the mechanical and curing properties of the tread blend had improved as the CR particle size reduced, with all of the mechanical and rheological properties reduction in a different manner when the CR content increased. The study revealed that the size reduction of CR could enhance the tensile strength up to 35%, and 17% for elongation at break for the finer size. To study the dynamic behavior of the tyre containing such modifyed CR, a finite element model based on Abaqus software was built as the second objective of the study. The model was used to study the effects of different particle size and content of CR on the traction, braking and slipping condition of the tyre. The parameters such as reaction force (rolling resistance), reaction moment, and pressure at footprint, stress, strain and strain energy were studied to figure out the complete behavior of the tyre at different tread properties. Finally, empirical models for tensile strength as a function of particle size and content of CR were built. Particle swarm optimization (PSO), and response surface method (RSM) based on design expert software were used. The results showed that both models have good accuracy in predicting the response, however the RSM model provided more accurate results. The statistical analysis confirmed that the effect of particle size was greater than the effect of content of CR on tensile strength of the tread.